Inventarisasi Tumbuhan Obat Di Kawasan Giribangun Girilayu Matesih Karanganyar Jawa Tengah - Salamah, Umi; , Dr. Sofyan Anif, M.Si (2017)
Giribangun is a hilly area that is used as one of the religious attractions of the large family funeral center of the President of the Republic of Indonesia, both the Great General of the TNI Muhammad Soeharto and Prince Samber Nyawa. These hills have a height of 660 meters above sea water demand with a high diversity of medicinal plants. Medicinal plants are all plants that all parts of the body can be used as a drug that can provide healing. The purpose of this research is to know the types of medicinal plants in Giribangun Girilayu area. The method used is exploration (Cruise / Methods Cruise) through the making of 15x5 meter plot by exploring all medicinal plants located in Giribangun area then recording and identifying medicinal plants on the setiaap of the lower and upper regions. The results of the study found 14 species of medicinal plants at an altitude of 330 m.dpl in dominance by the tribe Euphorbiaceae Sansevieria cylindrica. Selaginella doederleinii. While at 660 m.dpl dketinggian found 10 types of medicinal plants with tribes that dominate Asteraceae Eupatorium inulifolium H.B.K. Based on the research, it can be concluded that the more the area of the diversity of medicinal plants is getting less.